Perovskite solar cell with tin oxide electron transport layer prepared based on chemical bath deposition method and preparation method thereof
By using citric acid without thiol groups as a complexing agent and KIO3 for interface modification in perovskite solar cells, the problem of surface defects of the tin oxide electron transport layer is solved, and the performance of the device is significantly improved.
Patent Information
- Application Number
- CN202510002013.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In traditional perovskite solar cells, there are many surface defects in the tin oxide electron transport layer, which affects the electron transport process and leads to poor device performance.
Citric acid without thiol groups is used as a chemical linking agent to replace the traditional thiolacetic acid TGA and as a complexing agent. After preparing the tin oxide layer by chemical bath deposition method, KIO3 aqueous solution is used for interface modification to reduce surface oxygen vacancies defects.
Through the synergistic action of citric acid and KIO3, a tin oxide electron transport layer with better crystalline quality is obtained, which reduces surface defects, enhances the transportation capacity of the electron transport layer, and significantly improves the open circuit voltage and photoelectric conversion efficiency of perovskite solar cells.
Smart Images

Figure CN119816165A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of thin-film solar cells, and in particular relates to a perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method and a preparation method thereof. Background Art
[0002] Compared with other thin-film solar cell absorption layer materials, such as gallium arsenide (GaAs), cadmium telluride (CdTe), copper indium gallium selenide (CIGS), etc., perovskite cells are one of the most promising materials in the field of thin-film solar cells due to their excellent photoelectric conversion efficiency, low economic cost, high absorption coefficient and adjustable band gap. In recent years, the field of perovskite solar cells has achieved remarkable achievements, among which the efficiency of a single cell has exceeded 25.7%, which has greatly promoted the industrialization and commercialization of perovskite solar cells, making them an ideal candidate to replace traditional energy.
[0003] Perovskite solar cells are usually composed of a glass substrate, a transparent conductive electrode, an electron transport layer (ETL), a perovskite light absorbing layer, a hole transport layer, and a back electrode. Among these layers, the ETL is crucial for the transport of photogenerated electrons and the blocking of holes in perovskite. In nip-structured perovskite solar cells, tin oxide (SnO2) has become the most widely used ETL material due to its excellent electron mobility, UV stability, and low-temperature processability. At present, in most high-efficiency nip devices, SnO2 is prepared using a chemical bath deposition (CBD) method, while the traditional process requires the use of SnCl2·2H2O as the source of Sn in SnO2 and the use of thioglycolic acid TGA as a complexing agent to carry SnO2 to the surface of the FTO substrate. TGA is used as a chemical linker in the bath deposition process, and the thiol groups it carries will cause surface defects of tin oxide, resulting in complex behavior during electron transport, thereby affecting the overall performance of the device. Summary of the invention
[0004] Based on the problems existing in the current prior art, the present invention provides a perovskite solar cell and a preparation method thereof for preparing a tin oxide electron transport layer based on a chemical bath deposition method. The present invention uses thiol-free citric acid as a chemical linker, thereby avoiding the additional defects caused by the step of introducing a complexing agent. In addition, as a complexing agent, the binding energy between tin and sulfur is significantly weaker than the binding energy between tin and oxygen, so we believe that citric acid is a better complexing agent. By utilizing the strong interaction between citric acid and tin oxide, we believe that it can replace TGA as a complexing agent in traditional processes, and achieve the effect of improving the tin oxide interface, so that the tin oxide layer has better electron transport ability. In addition, SnCl2·2H2O is used as a tin source in the Sn 2+ Converted into Sn in the target product SnO2 4+During the CBD process, the problem of incomplete conversion may occur. Therefore, after the CBD process, we use KIO3 aqueous solution as an interface modification step to use the oxidizing property of KIO3 to promote the residual Sn on the surface of tin oxide. 2+ Convert to Sn 4+ , in order to achieve the effect of reducing surface oxygen vacancy defects and inhibiting the recombination behavior of carriers. Through the synergistic effect of citric acid and KIO3, a tin oxide electron transport layer with better crystal quality was obtained, which reduced surface defects, enhanced the transport capacity of the electron transport layer, and achieved a significant improvement in device performance.
[0005] The object of the present invention is to provide a method for preparing a perovskite solar cell with a tin oxide electron transport layer prepared by a chemical bath deposition method, wherein the solar cell improves the open circuit voltage of the perovskite solar cell device and thus improves the device performance.
[0006] To achieve the above object, the technical solution adopted by the present invention is: A perovskite solar cell with a tin oxide electron transport layer prepared by chemical bath deposition method, which consists of an Au electrode, a Spiro-OMeTAD hole transport layer, a perovskite light absorption layer, a SnO2 electron transport layer and a FTO substrate from top to bottom.
[0007] Furthermore, the Au electrode has a thickness of 80-100 nm.
[0008] Furthermore, the Spiro-OMeTAD layer is composed of Spiro-OMeTAD, Li salt, Co salt, and tributyl phosphate TBP, and has a thickness of 70-100 nm.
[0009] Furthermore, the perovskite light absorbing layer is FA 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl 0.06 The film has a thickness of 450~550nm.
[0010] Furthermore, the tin oxide electron transport layer is prepared by chemical bath deposition method, and its thickness is 50-100 nm.
[0011] Furthermore, the thickness of the FTO substrate is 350-400 nm.
[0012] The present invention also provides a method for preparing the above-mentioned perovskite solar cell using the chemical bath deposition method to prepare the electron transport layer, comprising the following steps: (1) Clean the FTO substrate and then blow dry it with nitrogen to obtain a clean substrate; (2) After preparing the precursor solution, a tin oxide layer is prepared by chemical bath deposition. Then, the tin oxide layer is treated by solution immersion method and annealed to obtain a SnO2 electron transport layer with a suitable grain size; (3) Preparing a perovskite layer on the SnO2 film, preparing a perovskite precursor film using an anti-solvent method, and obtaining a perovskite light-absorbing layer with good crystallinity after annealing; (4) Prepare the Spiro-OMeTAD hole transport layer on the perovskite layer by spin coating; (5) The Au electrode was deposited on the Spiro-OMeTAD hole transport layer using vacuum evaporation technology.
[0013] Furthermore, in step (2), the precursor solution includes SnCl2·2H2O, citric acid, urea and HCl.
[0014] Furthermore, in step (2), the solution used in the solution immersion method is a KIO3 aqueous solution.
[0015] Furthermore, in step (2), the annealing temperature is 180° C. and the annealing time is 1 hour.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The perovskite solar cell of the present invention, which uses a chemical bath deposition method to prepare a tin oxide electron transport layer, has an efficiency of more than 24.9%, and promotes the application process of perovskite solar cells; and it uses citric acid as a complexing agent in the synthesis step of the electron transport layer and uses a KIO3 aqueous solution as a surface modifier after the reaction is completed, and the synergistic effect of percitric acid and KIO3 obtains a tin oxide electron transport layer with better crystal quality, reduces surface defects, enhances the transport capacity of the electron transport layer, and achieves a significant improvement in device performance. At the same time, the preparation method of the present invention is simple and easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic structural diagram of a perovskite solar cell in which a tin oxide electron transport layer is prepared based on a chemical bath deposition method according to an embodiment of the present invention.
[0018] Figure 2 This is the preparation process of the tin oxide electron transport layer in the embodiment of the present invention.
[0019] Figure 3 3 is a SEM surface image of the tin oxide electron transport layer in an embodiment of the present invention.
[0020] Figure 4 FA in the present invention 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl0.06 SEM surface image of perovskite film.
[0021] Figure 5 FA in the present invention 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl 0.06 XRD patterns of the films.
[0022] Figure 6 The perovskite solar cell in which citric acid and KIO3 act synergistically on the tin oxide electron transport layer in the embodiment of the present invention, the perovskite solar cell using citric acid and the tin oxide electron transport layer not modified by KIO3, and the perovskite solar cell using TGA on the tin oxide electron transport layer in the conventional embodiment of the present invention are compared. JV curve. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0026] like Figure 1 As shown, this example provides a perovskite solar cell with a tin oxide electron transport layer prepared by chemical bath deposition.
[0027] In this embodiment, the Au electrode has a thickness of 80 nm. The Spiro-OMeTAD hole transport layer is composed of 100 mg Spiro-OMeTAD, 24.5 μL of 520 mg / mL Li salt acetonitrile solution, 49 μL of 300 mg / mL Co salt acetonitrile solution, and 40 μL of TBP, and its thickness is 70 nm. The perovskite light absorption layer is FA 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl 0.06The film has a thickness of 500nm, the tin oxide electron transport layer is prepared by chemical bath deposition method, and has a thickness of 80nm, and the FTO substrate has a thickness of 400nm.
[0028] In this embodiment, the preparation process of the perovskite solar cell using the chemical bath deposition method to prepare the electron transport layer is as follows: (1) Cleaning FTO substrate The samples were ultrasonically cleaned with deionized water, acetone, and anhydrous ethanol for 20 minutes each, dried with nitrogen, and then treated with UV-ozone.
[0029] (2) Preparation of electron transport layer The tin oxide layer is prepared by chemical bath deposition method, and then treated by solution immersion method and annealed to obtain a tin oxide layer with suitable grain size.
[0030] (201) Add 550 mg of SnCl2·2H2O, 20 mg of citric acid, and 1.2 mg of urea to 200 mL of ultrapure water and stir. During the stirring process, add 1.2 mL of 37 wt% concentrated hydrochloric acid until the solution is completely transparent.
[0031] (202) The clean FTO substrate was placed in the above solution, transferred to an oil bath, heated at 90 °C for 5.5 h, and then taken out and cooled to room temperature.
[0032] (203) The substrate after deposition was placed in a KIO3 aqueous solution, transferred to an oven for heating, and then the FTO was placed on an annealing table for annealing. Process parameters: KIO3 aqueous solution concentration of 2 mM; oven temperature of 60 °C, heating time of 10 min; annealing temperature of 180 °C, time of 1 hour, in an environment with a relative humidity of less than 40%.
[0033] Figure 2 This is a schematic diagram of the process of preparing a tin oxide electron transport layer by the chemical bath deposition method. Figure 3 This is the SEM image of the surface of the tin oxide electron transport layer after preparation.
[0034] (3) Preparation of FA by anti-solvent method 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl 0.06 Perovskite light absorbing layer, Figure 4 This is the SEM surface image of the film; Figure 5 This is the XRD pattern of the film.
[0035] (301) Weigh 8.9 mg of RbI, 11.1 mg of MAI, 45.4 mg of PbI2, 215.7 mg of FAI, and 11.8 mg of CsCl and dissolve them in a mixed solution of 800 μL of N,N-dimethylformamide (DMF) and 200 μL of dimethyl sulfoxide (DMSO), stir and filter before use. Process parameters: volume ratio of DMF to DMSO 4:1; stirring time 3-5 h; filter radius 0.22 μm.
[0036] (302) The FTO substrate after the reaction in step (2) is transferred to a coating machine, 45 μL of the above solution is taken to cover the surface and then spin-coated to prepare a precursor film of the perovskite light absorbing layer. After adding the anti-solvent, the precursor film is transferred to the annealing table for annealing. Process parameters: The spin coating process includes a. low speed stage, rotation speed 1000 rpm, acceleration 200 rapm, time is 10 seconds; b. high speed stage, rotation speed 4000 rpm, acceleration 2000 rapm, time is 30 seconds, and 110 μL of anti-solvent chlorobenzene is added at 25 seconds. The annealing temperature is 110°C and the time is 60 minutes.
[0037] (4) Preparation of Spiro-OMeTAD layer Weigh 100 mg of Spiro-OMeTAD powder, 24.5 μL of acetonitrile solution of 520 mg / mL lithium bis(fluorosulfonyl)imide, 49 μL of acetonitrile solution of 300 mg / mL tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridinium)cobalt(III)tris[bis(trifluoromethane)sulfonylimide], and 40 μL of TBP, stir and transfer 20 μL of the solution to the perovskite surface for spin coating. Process parameters: rotation speed 4000 rpm; acceleration 3000 rapm; time 30 seconds.
[0038] (5) Preparation of top Au electrode The top electrode is prepared by vacuum evaporation using a mask. Process parameters: vacuum degree is less than 1×10 -4 Pa, evaporation rate is 1 Å / s, deposition thickness is 80nm. Au electrode is 10% of the total area of solar cell.
[0039] like Figure 6 As shown in the figure, the open circuit voltage of the perovskite solar cell with an electron transport layer prepared by chemical bath deposition in this embodiment is 1.17V, and the short circuit current is 25.19mA / cm 2 The fill factor is 84.51% and the photoelectric conversion efficiency is 24.91%. The open circuit voltage of the perovskite solar cell using citric acid and a tin oxide electron transport layer without KIO3 modification is 1.14V and the short circuit current is 25.07mA / cm 2, the fill factor is 83.24%, and the photoelectric conversion efficiency is 23.82%. The open circuit voltage of the perovskite solar cell prepared by the traditional chemical bath deposition method based on TGA as a complexing agent is 1.12V, and the short circuit current is 24.87mA / cm 2 , the filling factor is 82.44%, and the photoelectric conversion efficiency is 22.96%. Compared with the perovskite solar cell with the electron transport layer prepared by the traditional chemical bath deposition method based on TGA as a complexing agent, the open circuit voltage of the perovskite solar cell with the electron transport layer prepared by the chemical bath deposition method of the present invention is significantly improved, thereby significantly improving the photoelectric conversion efficiency of the device by 1.95%.
[0040] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A perovskite solar cell with a tin oxide electron transport layer prepared by chemical bath deposition, characterized in that: The perovskite solar cell consists of an Au electrode, a Spiro-OMeTAD hole transport layer, a perovskite light absorption layer, a SnO2 electron transport layer and a FTO substrate from top to bottom.
2. A perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method according to claim 1, characterized in that: The Au electrode has a thickness of 80-100 nm.
3. A perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method according to claim 1, characterized in that: The Spiro-OMeTAD hole transport layer is composed of Spiro-OMeTAD, Li salt, Co salt, and tributyl phosphate TBP, and its thickness is 70~100nm.
4. A perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method according to claim 1, characterized in that: The perovskite light absorbing layer is FA 0.9 MA 0.05 Cs 0.05 PbI 2.94 Cl 0.06 The film has a thickness of 450~550nm.
5. A perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method according to claim 1, characterized in that: The SnO2 electron transport layer is prepared by chemical bath deposition method and has a thickness of 50-100 nm.
6. A perovskite solar cell for preparing a tin oxide electron transport layer based on a chemical bath deposition method according to claim 1, characterized in that: The thickness of the FTO substrate is 350-400 nm.
7. A method for preparing a perovskite solar cell using a tin oxide electron transport layer prepared by chemical bath deposition as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Clean the FTO substrate and then blow dry it with nitrogen to obtain a clean substrate; (2) After preparing the precursor solution, a tin oxide layer is prepared by a chemical bath deposition method, and then a solution immersion method is used for treatment and then annealing is performed to obtain a SnO2 electron transport layer; (3) Preparing a perovskite layer on the SnO2 film, preparing a perovskite precursor film using an anti-solvent method, and obtaining a perovskite light-absorbing layer with good crystallinity after annealing; (4) Prepare the Spiro-OMeTAD hole transport layer on the perovskite layer by spin coating; (5) The Au electrode was deposited on the Spiro-OMeTAD hole transport layer using vacuum evaporation technology.
8. A method for preparing a perovskite solar cell using a tin oxide electron transport layer prepared by chemical bath deposition according to claim 7, characterized in that: In step (2), the precursor solution includes SnCl2·2H2O, citric acid, urea and HCl.
9. A method for preparing a perovskite solar cell using a tin oxide electron transport layer prepared by chemical bath deposition according to claim 7, characterized in that: In step (2), the solution used in the solution immersion method is a KIO3 aqueous solution.
10. A method for preparing a perovskite solar cell using a tin oxide electron transport layer prepared by chemical bath deposition according to claim 7, characterized in that: In step (2), the annealing temperature is 180° C. and the annealing time is 1 hour.
Citation Information
Patent Citations
Method for preparing positive electrode material of alloy-reinforced anoxic stannic oxide nanosheet array supercapacitor
CN110600276A
Tin dioxide thin film, preparation method thereof and perovskite solar cell
CN116390619A
Perovskite solar cell repairing method based on external voltage intervention
CN118714896A